2020
DOI: 10.1039/d0cc04883f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cis- and enantioselective cyclopropanation of styrene catalysed by cytochrome P450BM3 using decoy molecules

Abstract: We report the enhanced cis- and enantioselective cyclopropanation of styrene catalysed by cytochrome P450BM3 in the presence of dummy substrates, i.e. decoy molecules. Molecular dynamics simulations underpin the experimental data,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…For instance, Arnold, Fasan, and Shoji groups have respectively reported that the T268A mutant of P450BM3 showed a drastic effect on the enantioselectivity in intramolecular C–H amination or cyclopropanation reactions. 21 We observed the substantial contribution of T268 mutations in regioselective demethylation for the oxidation of aromatic ethers by the DFSM-facilitated P450BM3 peroxygenase. 18 e Therefore, we hypothesized that merging the positive effect of Im-C6-Phe and the potential positive effect of T268 mutation will improve the ( R )-enantioselectivity of styrene epoxidation.…”
Section: Resultsmentioning
confidence: 71%
“…For instance, Arnold, Fasan, and Shoji groups have respectively reported that the T268A mutant of P450BM3 showed a drastic effect on the enantioselectivity in intramolecular C–H amination or cyclopropanation reactions. 21 We observed the substantial contribution of T268 mutations in regioselective demethylation for the oxidation of aromatic ethers by the DFSM-facilitated P450BM3 peroxygenase. 18 e Therefore, we hypothesized that merging the positive effect of Im-C6-Phe and the potential positive effect of T268 mutation will improve the ( R )-enantioselectivity of styrene epoxidation.…”
Section: Resultsmentioning
confidence: 71%
“…This substrate misrecognition system using decoy molecules has also been successfully expanded to P450BM3 monooxygenase in benzene hydroxylation, 15 high-pressure gas hydroxylation, 16 intracellular reactions, 17 and carbene insertion reactions. 18 The crystal structure of CYP152A1 binding to heptanoic acid (PDB: ) reveals that the carboxylate of heptanoic acid interacts with Arg242, permitting the generation of Compound I. 19 Owing to its short length, the oxidation of heptanoic acid does not proceed, making Compound I available for the oxidation of non-native substrates.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the reactivity for various non-native substrates, we employed previously reported substrate analogues (decoy molecules). Decoy molecules have been reported to activate P450BM3 for the oxidation of non-native substrates, such as ethane, , benzene, , cyclohexane, and styrene as well as modulate the stereoselectivity for prochiral substrates. , …”
Section: Resultsmentioning
confidence: 99%
“…Decoy molecules have been reported to activate P450BM3 for the oxidation of non-native substrates, such as ethane, 68,69 benzene, 41,70 cyclohexane, 43 and styrene as well as modulate the stereoselectivity for prochiral substrates. 42,71 In the presence of decoy molecules, Mn-BM3 I401P exhibited activity toward a rich variety of substrates, accomplishing the sulfoxidation of thioanisol, the epoxidation of styrene, and the hydroxylation of aliphatic, aromatic, and benzylic C−H bonds (Figure 4, Supplementary Tables S3− S9). Notably, Mn-BM3 I401P performed the hydroxylation of ethane, a notoriously challenging conversion owing to its high Radical Clock Experiments.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%